Comment on "Tunable Design of Structural Colors Produced by Pseudo‐1D Photonic Crystals of Graphene Oxide" and Thin‐Film Interference from Dried Graphene Oxide Film. Issue 15 (April 2017) - Hong, Seung‐Ho; Song, Jang‐Kun
Abstract : The mechanism of the iridescent color reflection from dried thin graphene oxide (GO) film on Si wafer is clarified. Dissimilarly to the photonic crystalline reflection in aqueous GO dispersion, the color reflection in dried GO film originates from the thin film interference. The peak reflection can reach 23% by optimizing the GO thickness and the substrate.